IMPLICATIONS OF NON-REIMBURSABLE FUNDS FOR ROMANIAN LOCAL BUDGETS - DAN CONSTANTIN DĂNULEŢIU; ADINA ELENA DĂNULEŢIU (Annals of the University of Petrosani: Economics)
Accessing non-reimbursable funds is seen as a solution for many local public authorities to develop the necessary investments for the welfare of their citizens. The paper analyzes the involvement of different categories of local public administrations in accession of non-reimbursable funds, seen by the reflection of these funds on the local budgets and shows the incidence of this involvement on their budgets. There are analyzed many indicators, such as the capacity of the local public authority to access non-reimbursable funds, the degree of covering the revenues received from EU/other donators from own local budget revenues, the weight of the expenditures for projects financed through EU funds in the total expenditures of local budgets and the capacity of financing expenditures for projects whose financing was provided by European non-reimbursable funds by own revenues. The paper concludes with some remarks for a better accession of non-reimbursable funds by local public administrations.